Design of Anastasia Private School Profile Website Using Waterfall Method - Maria Sere Vina Simatupang; Feriani Astuti Tarigan; Jakri Hendrik, (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
The development of information technology encourages educational institutions to utilize digital media as a means of delivering information, one of which is through a school profile website. Anastasia Private School located on Jl. Jamin Ginting has four levels of education, namely kindergarten, elementary school, junior high school, and high school. However, the current website is still not interactive and informative, making it difficult for the public to obtain complete information about the school. Reliance on traditional promotional media such as banners and brochures is no longer considered effective in building the image and attractiveness of schools in today's digital era. This study aims to design a profile website for Anastasia Private School that is more informative, interactive, and easily accessible to the wider community. The system development uses the Waterfall method, which consists of the stages of needs analysis, design, implementation, testing, and maintenance. This website is designed with eight main features, including Home, Profile, About Us, Academic, Gallery, News, and PPDB Info. The result of this research is a website that is able to present comprehensive information about the school, so that it can be an effective socialization media, strengthen the school's image, and facilitate the community in accessing the education information needed.